Reproductive efficiency and breeding potential of East African highland (Musa AAAEA) bananas - Ssebuliba, R.; Talengera, D.; Makumbi, Dan; Namanya, P.; Tenkouano, A.; Tushemereirwe, Wilberforce K.; Pillay, M. (Elsevier, 2006)
The East African highland banana (Musa spp. AAA) is an economically important food crop. The crop is affected by a number of diseases and pests. Genetic improvement of the crop is hindered by very low seed set and poor seed germination. The objective of this study was to compare seed set, seed quality and embryo rescue rates of hybrid seeds obtained from 20 East African highland banana cultivars crossed with a fertile diploid species, Musa acuminata spp. burmannicoides ‘Calcutta 4’, as a male parent. There was great variation in seed set, seed quality and in vitro embryo germination rates among the cultivars. Although 72% (range = 47–88%) of the seeds appeared normal externally characterized by black hard integuments, only 59% (range = 35–81%) contained embryos, of which 9% (range = 0–22%) germinated. This study demonstrated that hard-seededness alone does not signify the presence of an embryo and should not be regarded as a measure of seed fertility in East African highland bananas. Cultivars ‘Entukura’, ‘Enzirabahima’ and ‘Kabucuragye’ of the ‘Nfuuka’ clone set were superior in terms of seed set, presence of seeds with embryos and culturability of embryos. These cultivars are recommended as female parents for a crossing program in the improvement of East African highland bananas. The low embryo rescue rates suggest that hybrid seeds derived from East African highland banana possess factors that cause high embryo abortion. This may be ascribed to endosperm breakdown, which can release toxins.